2013
DOI: 10.1108/00368791311303465
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of micropolar lubricated lobe bearings: influence of non‐circularity parameters

Abstract: Purpose -The purpose of this paper is to analyse the static performance characteristics of lobe journal bearings lubricated with a micropolar fluid, considering effect of non-circularity. Number of lobes and their preload value are the non-circularity parameters considered in the present study. The bearings undertaken for the investigation are two, three and four-lobe symmetric journal bearings with finite width. Design/methodology/approach -For this purpose, modified form of Reynolds equation is derived, base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Nekoeimehr et al. 15 used the micropolar fluid theory for the study of various geometries of non-circular bearing, i.e., effect of non-circularity parameters on the performance of lobed bearings. They concluded that performance of such bearings is dependent on the number of lobes and preload values.…”
Section: Introductionmentioning
confidence: 99%
“…Nekoeimehr et al. 15 used the micropolar fluid theory for the study of various geometries of non-circular bearing, i.e., effect of non-circularity parameters on the performance of lobed bearings. They concluded that performance of such bearings is dependent on the number of lobes and preload values.…”
Section: Introductionmentioning
confidence: 99%
“…Nekoeimehr et al. 7 presented the effect of non-circularity parameters on lobed bearings. They found that the number of lobes and their preload values are the key factors which affect the performance of such bearings.…”
Section: Introductionmentioning
confidence: 99%
“…Research studies [6][7][8][9][10][11][12][13][14] in the area of non-circular bearings are discussed below. Non-circular bearings (two-lobe, three-lobe and four-lobe bearings) were examined by Rahmatabadi et al 6 They evaluated various static characteristics of these bearings and compared them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the performance of bearings can be enhanced by selecting the proper bearing orientation angle. Recently, Nekoeimehr et al [13] presented an analysis of lobe bearings under micropolar lubrication. Later on, Sharma and Ram [14] analyzed influence of parameters of micropolar lubricant on symmetric slot-entry hybrid journal bearing.…”
Section: Introductionmentioning
confidence: 99%